Portrayals the Ideal Men’s Body through the Body’s Nutritional Products - Teguh Dwi Putranto (Jurnal Komunikasi Profesional, 2022)
The body becomes an object that continues to change in the direction desired by each human being so that everyone has different goals and efforts in determining the purposes of their respective bodies. This is reinforced by the concept of the body being disorganized so that the capitalist industry uses this opportunity to discipline the body. Based on this background, this study aims to discover how the @lmen Instagram post evokes fantasies in men's minds through the signs that appear in @lmen's Instagram posts. The method used in this research is Charles Sanders Peirce's semiotics of 5 selected @lmen Instagram posts during 2020, which features a model represented by the winner of The New L-Men of the Year with L-Men products in one post. The conclusion obtained in this study is that men's body image with arm muscles and healthy skin is dominated by the consumption of L-Men as a body nutrition product.